Ocean prey - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel., 2021)
Picking up a stalled FBI case involving three murdered Coast Guardsmen, Lucas Davenport teams up with detective Virgil Flowers to investigate the suspicious activities of a sophisticated boat and mysterious diver.